2022
DOI: 10.1101/2022.03.14.483550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic model of bovine brucellosis to investigate control strategies in endemic settings

Abstract: Brucellosis imposes substantial impacts on livestock production and public health worldwide. A stochastic, age-structured model incorporating herd demographics was developed describing within- and between- herd transmission of Brucella abortus in dairy cattle herds. The model was fitted to data from a cross-sectional study conducted in Punjab State of India and used to evaluate the effectiveness of control strategies under consideration. Based on model results, stakeholder acceptance and constraints regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Finally, to increase precision of the estimate, a design effect of 1.56 was applied giving a minimum sample size of 210 herds (n 2 ). This design effect was assumed considering the absence of any previous similar study conducted in the country that can be used to calculate cluster variance values, hence we referred the value used in a similar study conducted by Holt et al (28) and the rule-of-thumb suggested by others (29,30).…”
Section: Sampling Design and Sample Sizementioning
confidence: 99%
“…Finally, to increase precision of the estimate, a design effect of 1.56 was applied giving a minimum sample size of 210 herds (n 2 ). This design effect was assumed considering the absence of any previous similar study conducted in the country that can be used to calculate cluster variance values, hence we referred the value used in a similar study conducted by Holt et al (28) and the rule-of-thumb suggested by others (29,30).…”
Section: Sampling Design and Sample Sizementioning
confidence: 99%